Embodiment of ecofeminist ethics in Adichie’s Purple hibiscus - Upadhyay, Toya; Sharma, Kamal (Nepal Journal of Multidisciplinary Research, 2024)
Background: The contemporary anthropocentric and patriarchal mindset has pervasively influenced the social and ecological justice system. Women and the Mother Earth have equally suffered injustice at the hands of males. Objective: In this background, this paper reads Chimamanda Ngozi Adichie’s novel Purple hibiscus (2003) to examine how it reflects the implications of ecofeminist ethics for the solution to the current social and ecological injustice. Method: Based on qualitative research design, the research employs textual analysis method to interpret the text to reach to conclusion. For textual analysis, it borrows theoretical insights from ecofeminism, basically, Karen Warren’s ideas of ‘ecofeminist ethics, and ‘justice for all. Finding: After analyzing the novel from the ecofeminist perspective, the research finds that it embraces ecofeminist ethics and justice for all principle by presenting three female characters: Kambili, Ifeoma, and Beatrice, who resolutely resist the dominant capitalism-motivated patriarchal ideology. Conclusion: The research concludes that the novel underscores the need and relevancy of ecofeminist ethics as well as the embodiment of Gaia principle and motherhood environmentalism to solve the current problem of social and ecological injustice. Critical reading of Purple hibiscus from the perspective of ecofeminist ethics marks a new endeavor. Novelty: The research will contribute to the understanding of human-nature interconnectedness and solving the current problem of social and environmental injustice.